2015
DOI: 10.1177/0081246315579323
|View full text |Cite
|
Sign up to set email alerts
|

Family cancer caregiving in urban Africa: interrogating the Kenyan model

Abstract: This article interrogates the complexities of the family cancer caregiver role in an urban (Nairobi) context within the framework of the model of palliative care in sub-Saharan Africa. Individual interviews and focus groups were utilized to explore the phenomenon of family cancer caregiving. Data were analysed from an interpretative phenomenological approach. Emergent themes demonstrate the ambiguities inherent in the cultural context of cosmopolitan Nairobi where, in addition to their traditional designated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Poor symptom management leads to functional decline, further loss of independence and greater reliance on social networks for material support. The financial burden of accumulating health care and basic needs cost as well as needing to take time away from work may significantly reduce the capacity of family members to offer long term informal care [ 34 ]. From bereavement interviews we found that some patients received little help from their families as their condition deteriorated and as they became increasingly dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Poor symptom management leads to functional decline, further loss of independence and greater reliance on social networks for material support. The financial burden of accumulating health care and basic needs cost as well as needing to take time away from work may significantly reduce the capacity of family members to offer long term informal care [ 34 ]. From bereavement interviews we found that some patients received little help from their families as their condition deteriorated and as they became increasingly dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Familial obligation was often framed around a cultural requirement, loyalty/setting as an example for younger family members, reciprocity/marital responsibility, and lacking any other choice [25,30,34,47]. Several studies cited cultural viewpoints of caregiving as a woman's role, although men undertake the role where a woman family member is not available [25,29,33,47,48].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Women, aged between 30-40 [7,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], spouses, children, and siblings [7, 23-26, 28, 30-49] Who do they care for?…”
Section: Who Are Informal Carers?mentioning
confidence: 99%
See 2 more Smart Citations